When parents die: locating children's right to economic security in South Africa's law of succession and guardianship - Cheng, Grace (Department of Private Law, 2021)
South Africa's era as a constitutional democracy has coincided with the recognition of children as independent rights-holders within its legal system. Signature and ratification of the Convention on the Rights of the Child (CRC) and the African Charter on the Rights and Welfare of the Child (ACRWC) demonstrated the Republic's commitment to children's rights on the international stage. South Africa's Constitution features a dedicated section on children's rights, and enshrines the principle that the best interests of the child are ‘of paramount importance' in every matter concerning the child. Whereas Roman-Dutch and English law historically conceptualised children as their parents' property or as conduits of family property, children today enjoy enforceable legal rights to property and material support. South African law has decisively deemed the interests of children worthy of constitutional protection as legal rights. Children's rights encompass both their need for protection and their right to autonomy. In the celebrated words of Justice Sachs, in contemporary South Africa every child is to be ‘constitutionally imagined' as an individual with inherent dignity, ‘not merely as a miniature adult waiting to reach full size' or ‘a mere extension of his or her parents, umbilically destined to sink or swim with them.'